Humanitarian Assistance and the Role of Customs in Expediting Aid Consignments across Borders - Kokkengada, Subramani Muthanna (2014)
ABSTRACT Humanitarian Assistance is a continuous ongoing process considering the frequent rise in cases of natural disasters and man-made disasters. Why do we need Humanitarian assistance? What is its purpose? The after effects of a disaster always gives rise to chaos which needs to be addressed in a quick manner and this is where the assistance of humanitarian groups is much needed. It can be broken down into emergency response and rehabilitation and development which can be denoted as short and long term assistance respectively. Customs play an important role in the entry and exit of all cargo across borders. In the case of humanitarian aid consignments there exists a lot of procedures and documentation which have to be given a lot of importance when considering the clearance of these consignments as their requirement is a necessity to those vulnerable during the aftermath, thus the legal frame work along with steps taken by humanitarians to make the entire process less tedious and more smooth are explained in detail through this dissertation. The case of Haiti has been considered to take a look at the working of Humanitarian assistance groups and the way they dealt with the situation at hand and how help was received from across the world but the means to reach it to the survivors was the toughest part of the entire operation, what the customs procedures were in order for consignments to enter and be received by the Haitian population is also been focused at in the dissertation. The challenges faced and the recommendations for those have been pointed out in the last part of this dissertation focusing on all aspects from donor and stakeholder liability to humanitarian logistics and delivery to affected people along with follow up and capacity building and what can be done by humanitarians in order to ensure that aid is delivered in a way that the chief ideologies of humanitarians namely impartiality and neutrality is always maintained or followed when assistance is offered.